2009
DOI: 10.1029/2008gl036377
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of bare soil albedo to surface soil moisture on the moraine of the Zongo glacier (Bolivia)

Abstract: International audienceThe dependence of bare soil albedo on soil water content is investigated using in situ data collected on the moraine of an Andean glacier (Bolivia). This study demonstrates a high negative correlation between the two variables that is best approximated by an exponential function, in agreement with previous studies. More importantly, the average snow-free albedo value during the rainy season is 40% lower than during the dry season (0.16 vs. 0.26). These results are relevant for climate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 23 publications
(24 reference statements)
2
30
0
1
Order By: Relevance
“…Future applications are certainly possible, especially considering the low cost, the autonomy of the LCA in terms of energy, and the very small size of the sensors. For example, the LCA could be useful to spatialize in situ albedos in glacierized catchments both on the glacier, where the evolution of the snow cover can be monitored, and in the non-glacierized part for the evolution of the seasonal snow cover and, more generally, the changes in the ground albedo due to, for example, variations in the soil moisture (Gascoin et al, 2009). The comparison between the LCA measurements and LANDSAT images during the period extending from 18 October 2015 to 30 June 2016 showed that the LCA is a powerful tool that can be used to quantify the evolution of the albedo index and characterize the surface state of the glacier by distinguishing between fresh snow, dirty snow, and ice.…”
Section: Discussionmentioning
confidence: 99%
“…Future applications are certainly possible, especially considering the low cost, the autonomy of the LCA in terms of energy, and the very small size of the sensors. For example, the LCA could be useful to spatialize in situ albedos in glacierized catchments both on the glacier, where the evolution of the snow cover can be monitored, and in the non-glacierized part for the evolution of the seasonal snow cover and, more generally, the changes in the ground albedo due to, for example, variations in the soil moisture (Gascoin et al, 2009). The comparison between the LCA measurements and LANDSAT images during the period extending from 18 October 2015 to 30 June 2016 showed that the LCA is a powerful tool that can be used to quantify the evolution of the albedo index and characterize the surface state of the glacier by distinguishing between fresh snow, dirty snow, and ice.…”
Section: Discussionmentioning
confidence: 99%
“…Domingo et al, 2000;Lobell and Asner, 2002;Gascoin et al, 2009). This limitation is justified for two reasons: First, soil hydrology is represented by a rather crude bucket model in JSBACH of 1 m depth, while albedo is only affected by soil water if the upper few millimetres to centimetres of the soil are wet (Gascoin et al, 2009). This effect can thus not be included in the current version of JSBACH in an appropriate way.…”
Section: Dynamic Background Albedomentioning
confidence: 99%
“…But Idso et al 's [1975] work has been challenged by more recent studies which indicated that, for many soil types, a nonlinear exponential relationship is more appropriate to depict the dependence of bare soil albedo on water content [ Duke and Guérif , 1998; Liu et al , 2002; Lobell and Asner , 2002; Wang et al , 2005; Gascoin et al , 2009a].…”
Section: Introductionmentioning
confidence: 99%